2014
DOI: 10.1002/ccd.25749
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, development, implementation, and initial results of a fast track protocol for transfemoral transcatheter aortic valve replacement (TAVR)

Abstract: Background: The care pathway for patients undergoing transcatheter aortic valve replacement (TAVR), particularly in the US, was initially based on open surgical techniques and often includes general anesthesia, transesophageal echocardiographic monitoring, and cardiothoracic intensive care unit (ICU) stays. Whether a subgroup of patients could benefit from early extubation, fewer days in the ICU, and early ambulation in terms of both cost and effectiveness is unknown. Methods and Results: A fast track (FT) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…The centers performing TAVR in the CoreValve U.S. trial were all new to the intervention, and extra precautions may have been taken in the context of an investigational device exemption trial. It is reasonable to expect that iterative improvements in TAVR technology in the short to intermediate term, coupled with increased clinical experience, will lead to reduced complication rates (21), more efficient care (22), reduced costs (23), and improved cost-effectiveness relative to SAVR, a much more mature therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The centers performing TAVR in the CoreValve U.S. trial were all new to the intervention, and extra precautions may have been taken in the context of an investigational device exemption trial. It is reasonable to expect that iterative improvements in TAVR technology in the short to intermediate term, coupled with increased clinical experience, will lead to reduced complication rates (21), more efficient care (22), reduced costs (23), and improved cost-effectiveness relative to SAVR, a much more mature therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of EDC (≤3 days) after TF TAVR with the SAPIEN XT prosthesis, no significant difference in the combined primary end point of 30-day death and rehospitalization was found between the early and late discharge groups. 8 Marcantuono et al 32 reported the implementation of a preassigned fast track TF TAVR protocol with the achievement of shorter LOS of 3.8 days compared with their center's 7.2 days for standard care.…”
Section: Summary Of the Experience Future Directions And Challengesmentioning
confidence: 99%
“…Several recent studies and registries from outside the United States have demonstrated the feasibility, safety, and cost savings associated with the avoidance of general anesthesia and implementation of fast-track protocols. 15,16 Increased use of these minimalist approaches to transfemoral TAVR, particularly well suited to SAPIEN 3, may represent an opportunity to further improve outcomes with this device in the current era. Alternatively, it is possible that the high use of transesophageal echocardiography guidance for sizing and postimplantation optimization contributed to the observed high success rates.…”
mentioning
confidence: 99%